ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEPATUHAN WAJIB PAJAK ORANG PRIBADI DALAM MEMENUHI KEWAJIBAN MEMBAYAR PAJAK KENDARAAN BERMOTOR (PKB) - Sauddin, Adnan; Kasse, Irwan; Z, Eldasari (Universitas Islam Negeri Alauddin Makassar, 2019)
In this article, discussed the factors that influence individual taxpayer compliance to pay vehicles tax such as motorcycle, car, and truck. The growth in the number of vehicles increasing rapidly, related to what is a problem in paying vehicles tax. There are several reasons, including taxpayer compliance to pay vehicles tax. In this article, there are 18 measurement indicators that influencing of this object. These measurement indicators then grouped into several factors using Exploratory Factor Analysis (EFA). The results showed that there were five factors that influenced taxpayer compliance to pay vehicles tax. The first factor is service quality, the second factor is spatial planning and tax administration, the third factor is tax socialization, the fourth factor is knowledge and understanding of taxation, and the fifth factor is education